2005
DOI: 10.1038/sj.leu.2403641
|View full text |Cite
|
Sign up to set email alerts
|

RAS mutation is associated with hyperdiploidy and parental characteristics in pediatric acute lymphoblastic leukemia

Abstract: We explored the relationship of RAS gene mutations with epidemiologic and cytogenetic factors in a case series of children with leukemia. Diagnostic bone marrow samples from 191 incident leukemia cases from the Northern California Childhood Leukemia Study were typed for NRAS and KRAS codon 12 and 13 mutations. A total of 38 cases (20%) harbored RAS mutations. Among the 142 B-cell acute lymphoblastic leukemia (ALL) cases, RAS mutations were more common among Hispanic children (P ¼ 0.11) or children born to moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 32 publications
10
58
1
1
Order By: Relevance
“…Although mutations in the FLT3, NRAS, KRAS, and PTPN11 genes have been suggested to be particularly common in high hyperdiploid childhood ALLs (Armstrong et al, 2004;Taketani et al, 2004;Tartaglia et al, 2005;Wiemels et al, 2005), the previous studies have been small, with Armstrong et al (2004), Taketani et al (2004), and Wiemels et al (2005) investigating only 25, 19, and 56 high hyperdiploid cases, respectively. Tartaglia et al (2004) included 102 pediatric BCP ALLs with a DNA index >1.0, but did not specifically delineate the high hyperdiploid subgroup.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Although mutations in the FLT3, NRAS, KRAS, and PTPN11 genes have been suggested to be particularly common in high hyperdiploid childhood ALLs (Armstrong et al, 2004;Taketani et al, 2004;Tartaglia et al, 2005;Wiemels et al, 2005), the previous studies have been small, with Armstrong et al (2004), Taketani et al (2004), and Wiemels et al (2005) investigating only 25, 19, and 56 high hyperdiploid cases, respectively. Tartaglia et al (2004) included 102 pediatric BCP ALLs with a DNA index >1.0, but did not specifically delineate the high hyperdiploid subgroup.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Wiemels et al (2005) suggested that RAS mutations are associated with high hyperdiploidy, identifying mutations in codons 12/13 in one of the genes in 30% (17/56) of cases. In addition, Tartaglia et al (2004) found an increased prevalence of RAS mutations in cases with a DNA index >1; however, they did not provide any frequency data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RAS mutations have been consistently correlated with myeloid leukaemias in adults and children, in particular with occupationallyassociated adult myeloid leukemias (Taylor et al, 1992;Barletta et al, 2004). Wiemels et al (2005) studied the relationship of RAS mutations, hyperdiploidy (> 50 chromosomes) and smoking in a case series of 191 acute leukaemia. Smoking was negatively associated with hyperdiploidy (possibly due to the sensitivity of the hyperdiploid clone and consequent differential survival) and hyperdiploid acute leukaemia cases had the highest rates of RAS mutations.…”
Section: (C) Effect Modificationmentioning
confidence: 99%